2017
DOI: 10.1007/s13197-017-2591-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different hydrocolloids to improve dough rheological properties and bread quality of potato–wheat flour

Abstract: The aim of study was to investigate the effect of hydroxylpropylmethylcellulose (HPMC), arabic gum (AG), konjac glucomannan (KG) and apple pectin (AP) at 2% (w/w, potato-wheat flour basis) on the potato-wheat dough (the mass ratio was 1:1) rheological, fermentation and bread making properties. The tan δ of potato-wheat dough was significantly increased upon addition of adding HPMC which was close to wheat dough (0.531). Moreover, dough height during fermentation process was significantly improved on addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Liu et al . (, ) also observed that hydrocolloid addition limited bread staleness, owing to the limitation of water mobility, thus influencing the gelatinisation process by decreasing the ∆ H . This result was also proved by that fibre hindered starch swelling because of limiting the water mobility of the ungelatinised granules (Rosell et al ., ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Liu et al . (, ) also observed that hydrocolloid addition limited bread staleness, owing to the limitation of water mobility, thus influencing the gelatinisation process by decreasing the ∆ H . This result was also proved by that fibre hindered starch swelling because of limiting the water mobility of the ungelatinised granules (Rosell et al ., ).…”
Section: Resultsmentioning
confidence: 91%
“…Similar results have also been demonstrated by Liu et al . (, ), who have found that mixing under vacuum increased the large polymeric protein and glutenin macropolymer content. The results can also be ascribed to the electrostatic and hydrophobic interactions between different ingredients.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…With the increasing awareness of health, there recently became a trend of “staplization” of minor grains, potato, or maize by introducing them into the system of staple foods dominated by wheat and rice. Such attempts were mostly focused on gluten‐free bread from minor grain, potato, and maize, or composite bread mixed with wheat (Brites, Trigo, Santos, Collar, & Rosell, ; Liu et al, ). However, the dilution and disruption of gluten network in a composite dough could decrease consistency, cohesiveness, and extensibility of the dough, and result in quality deterioration of bread on texture, taste, shelf life, appearance, and specific volume (Jafari, Koocheki, & Milani, ; Moore, Juga, Schober, & Arendt, ).…”
Section: Introductionmentioning
confidence: 99%